How to avoid a swift kick in the chameleons - Padilla, Antonio; Platts, Emma; Stefanyszyn, David; Walters, Anthony; Weltman, Amanda; Wilson, Toby (IOP Publishing, 2016)
Recently, it was argued that the conformal coupling of the chameleon to matter fields created an issue for early universe cosmology. As standard model degrees of freedom become non-relativistic in the early universe, the chameleon is attracted towards a “surfing'' solution, so that it arrives at the potential minimum with too large a velocity. This leads to rapid variations in the chameleon's mass and excitation of high energy modes, casting doubts on the classical treatment at Big Bang Nucleosynthesis. Here we present the DBI chameleon, a consistent high energy modification of the chameleon theory that dynamically renders it weakly coupled to matter during the early universe thereby eliminating the adverse effects of the `kicks'. This is done without any fine tuning of the coupling between the chameleon and matter fields, and retains its screening ability in the solar system. We demonstrate this explicitly with a combination of analytic and numerical results.